Effect of alpha-actinin-3 gene on trained and untrained Turkish middle-school children's sprinting performance: a pilot study - GÜNEY, AHMET İLTER (TAYLOR & FRANCIS LTD, 2014)
ACTN3 R577X polymorphism was evaluated in trained and untrained Turkish middle-school children's sprinting performance. Twenty trained and 30 untrained children were genotyped; the frequencies of RR, RX and XX genotypes were 65, 30 and 5% in the trained individuals and 50, 27 and 23% in the controls ( untrained), respectively. The R allele was present in 80% of the trained and 63% of the untrained individuals, whereas the X allele was present in 20% of the trained and 37% of the untrained individuals. The average values of time taken for running 50 m for the trained and untrained groups were 10.21 +/- 0.68 and 11.88 +/- 1.18 s in RR genotypes, and 10.48 +/- 0.54 and 12.28 +/- 1.26 s in RX genotypes, respectively. These differences were statistically significant and ecologically meaningful. Such polymorphism may form an informative criterion for identifying individuals who might become talented sprinters with suitable training.
Keywords: athletic performance; sports genetics; ACTN3; polymorphism; ATHLETIC PERFORMANCE; ACTN3 GENOTYPE; POLYMORPHISM; ASSOCIATION; DEFICIENCY; EVOLUTION; STRENGTH